2018
DOI: 10.1136/bmjopen-2017-021339
|View full text |Cite
|
Sign up to set email alerts
|

Drivers and strategies for avoiding overuse. A cross-sectional study to explore the experience of Spanish primary care providers handling uncertainty and patients’ requests

Abstract: ObjectivesIdentify the sources of overuse from the point of view of the Spanish primary care professionals, and analyse the frequency of overuse due to pressure from patients in addition to the responses when professionals face these demands.DesignA cross-sectional study.SettingPrimary care in Spain.ParticipantsA non-randomised sample of 2201 providers (general practitioners, paediatricians and nurses) was recruited during the survey.Primary and secondary outcome measuresThe frequency, causes and responsibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 39 publications
5
30
0
2
Order By: Relevance
“…In so doing, they described many clinician-identified drivers of overuse, including insulation from costs, fears of "missing something," and patient demands. [36][37][38] Often, the "yes, but" phenomenon revealed participants' disbelief that overuse can cause nontrivial harms, which is consistent with research showing that clinicians often underestimate interventions' harms and overestimate benefits. 39 Our findings contrast with those of a recent survey evaluating physician attitudes toward financial penalties to deter use of low-value services.…”
Section: Discussionsupporting
confidence: 58%
“…In so doing, they described many clinician-identified drivers of overuse, including insulation from costs, fears of "missing something," and patient demands. [36][37][38] Often, the "yes, but" phenomenon revealed participants' disbelief that overuse can cause nontrivial harms, which is consistent with research showing that clinicians often underestimate interventions' harms and overestimate benefits. 39 Our findings contrast with those of a recent survey evaluating physician attitudes toward financial penalties to deter use of low-value services.…”
Section: Discussionsupporting
confidence: 58%
“…14 15 A study in Spain among GPs, nurses and paediatricians identified also lack of time as a crucial barrier, next to insufficient patient information. 16 A Swiss survey showed that GPs saw the specific request of patients as the most important barrier; time constraints and fear for malpractice suits were hardly mentioned. 17 A Dutch study identified the demand-satisfying attitude and the available diagnostic facilities as the most prominent barriers for GPs to avoid low-value care practices.…”
Section: Introductionmentioning
confidence: 99%
“…The literature reflects the outcome of interventions based on communication of the benefit of following these recommendations, acting on professional attitudes, knowledge, and behavior, or on changes in patient demands [25,26]. For example, the results of the Choosing Wisely campaign are inconsistent; while significant reductions in some "Do not Do" practices have been achieved, there has been no change in the implementations of others by professionals [27,28].…”
Section: Discussionmentioning
confidence: 99%